Advanced fibre optic sensor (crack detector) / Nurain Syuhana Muhamad Zaini and Anas Zafirol Abdullah Halim - Muhamad Zaini, Nurain Syuhana; Abdullah Halim, Anas Zafirol (2023)
Structural defects such as cracks are one of the most critical issues that can arise at any phase of construction. Detecting concrete cracks may be difficult because they often occur beneath the surface. The use of fibre optic sensors was first introduced to detect cracks that occur in concrete. The aims of this innovation project are to develop an advanced fibre optic sensor design idea, assemble the prototype from the improvised design, demonstrate its performance, and assess its marketability potential. Secondary data collection methods were used to gather information from previous studies. Based on this research, it is noted that the efficiency of fibre optic sensors can be affected by various factors such as the expensive cost of fibre optic cables, even though they have the capability to detect cracks in buildings. By identifying these key problems, this study offers an opportunity to propose innovative solutions.